Bus service in Damansara and its surrounding areas (Sri Jaya no.244) / Rozainor Mohd. Yunus - Mohd. Yunus, Rozainor (1994)
The objective of the research is to identify problems faced by the S.J Kenderaan Sdn. Bhd. and to suggest recommendations for improvement in the service level, including routes and scheduling. A survey is made using structured questionnaires to seek the views of the passengers, residents, operator and the employees of the company. At the conclusion of the research, it is found that the bus service is poor; running out of schedule thus causing the bus service (service no. 244) losing its passengers. To increase the number of passengers using the service, a number of improvements must be implemented and this will be further described at the conclusion of this research.